ON THE HOCHSCHILD HOMOLOGY OF INVOLUTIVE ALGEBRAS - Jeffrey Giansiracusa (Glasgow Mathematical Journal, 2018)
We study the homological algebra of bimodules over involutive associative algebras. We show that Braun’s definition of involutive Hochschild cohomology in terms of the complex of involution-preserving derivations is indeed computing a derived functor: the Z/2-invariants intersected with the center. We then introduce the corresponding involutive Hochschild homology theory and describe it as the derived functor of the pushout of Z/2-coinvariants and abelianization.